Integrasi Simulasi untuk Analisis Aliran Daya Sirkit Transmisi Kedinding–Bangkalan - Kiswantono, Agus (INTER TECH, 2025)
This study analyzes the power flow in the 150 kV Kedinding–Bangkalan Transmission Circuit using two simulation platforms, ETAP and MATLAB Simulink, to evaluate the performance of the transmission system and ensure the sustainability of the electrical power supply. Power flow analysis is essential in electrical systems to determine steady-state conditions, including voltage, current, active power, and reactive power. The Kedinding–Bangkalan circuit plays a crucial role in the stability of the electricity supply to Madura Island, which relies on energy from Java Island. The objective of this study is to compare the simulation results between ETAP, which uses the Newton-Raphson method for high accuracy, and MATLAB Simulink, which is more flexible in dynamic modeling. The simulation results show that the voltage profiles from both platforms are highly consistent, with minimal differences in active and reactive power (less than 2%). ETAP's simulation slightly underestimates the power loss (around 1.5%) compared to Simulink, but both show good stability under full load and fault conditions, with respective power losses recorded at 3.2% and 3.5%. These results indicate that both platforms can be used together to obtain a more comprehensive view of the transmission system's performance. Their integration allows for the exploration of more complex scenarios, such as load variations and faults, while enhancing simulation accuracy. This research is expected to contribute to the development of more effective and adaptive transmission system analysis methods, strengthening the reliability and efficiency of power systems, and supporting decision-making in transmission network planning and management